A note on fully homomorphic encryption of real-life data. Issue 4 (2nd October 2021) - Kahrobaei, Delaram; Shpilrain, Vladimir
Abstract : The purpose of this short paper is to explain the difference between encrypting real-life data and encrypting elements with a ring structure in the context of fully homomorphic encryption (FHE). Specifically, our encryption of real-life data is in two stages. First, we use a private-key embedding of real-life data in a ring; this embedding does not have to be fully homomorphic. This private embedding, speaking informally, takes most of the security burden off the second part of our encryption procedure, namely FHE between rings. The whole encryption function is then not fully homomorphic, but we show that it still provides for the most popular functionalities one expects from FHE, including private search on encrypted data.